Variasi Respon Pembentukan IgY terhadap Toxoid Tetanus dalam Serum dan Kuning Telur pada Individu Ayam Petelur - Teguh Wibawan, I Wayan; Bayu Prakoso Darmono, Iman; Suartha, I Nyoman (Jurnal Veteriner; Vol 11 No 3 (2010), 2010)
The variation of response on the production of specific IgY to tetanus toxoid among chickenin serum and egg yolk was observed in this study. Chicken showed relatively late response inproducing specific IgY in serum, around 59 days were needed to have a positive precipitationreaction of complex IgY-tetanus toxoid in the immunodiffusion test (agar gel precipitation test/AGPT). The presence of IgY in egg yolk could be detected one week after positive reations inserum was observed. The positive reaction in AGPT mostly related with the positive reaction inELISA, eventhough the variation of titer values were observed among chicken sera and egg yolk.This response variation might be related with the different of physiological status of the chicken.
Keywords: Variation of response, IgY, serum, egg yolk, toxoid tetanus